Clinical and Epidemiological Study on Tubercular Uveitis in a Tertiary Eye Care Centre in Italy - M. La Cava; A. Bruscolini; M. Sacchetti; M. P. Pirraglia; A. Moramarco; M. Marenco; G. Iaiani; G. Covelli; T. Rizzo; I. Abicca; A. Lambiase (Journal of Ophthalmology)
Purpose. To describe frequency, clinical characteristics, and visual prognosis of tubercular uveitis (TBU) in a nonendemic country. Methods. We retrospectively reviewed 3743 charts of patients with endogenous uveitis visited from 2008 to 2018 at a tertiary referral centre in Rome, Italy. We included immunocompetent patients with diagnosis of TBU. Patients were divided in two groups: patients with history of uveitis without a previous diagnosis of TBU (group A) and patients at their first episode of TB uveitis (group B). Results. TBU was diagnosed in 28 (0.75%) out of 3743 patients. Twelve (42.9%) patients came from tuberculosis endemic areas. All patients received specific antitubercular treatment (ATT) and were evaluated for a mean follow-up of 3.2 ± 2.9 years. Group A showed a greater number of ocular complications when compared with group B. ATT was effective in reducing the frequency of recurrences of uveitis in patients of group B. Conclusion. Intraocular inflammation can be the first manifestation of tuberculosis. Our data highlight that early diagnosis and specific treatment of TBU may allow to decrease recurrences and to improve visual outcomes.